(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2019)
Background: In order to improve the prescription quality and promoting rational prescription pattern, there is an obligatory need to investigate the factors that affect doctors’ prescription patterns. The study was conducted to observe the antibiotics prescribing pattern at outpatient department of a tertiary medical college hospital. Methods: This was a descriptive cross sectional study in a tertiary medical college hospital during the period of January 2018 to June 2018 which was conducted on 300 prescriptions collected from different outpatient department. Results: Average number of drugs prescribed per encounter was 3.70 (Optimal value 1.6–1.8). Antibiotics (Oral, injectable and topical) were prescribed 46% (Optimal value 20.0–26.8%) and antibiotic as only injected form 19.71% (Optimal value 13.4–24.1% of total injectable drug). Drugs prescribed from the Essential Drugs List( EDL) equated to 52.90% (Optimal value 100%). The antibiotics given in most of the patients ( 91%) were without doing culture sensitivity test before prescribing. Out of 46% prescriptions with antibiotics, 79.9% had one antibiotic, 19.6% included two antibiotics and 0.7% had three antibiotics. Cefuroxime was the most commonly prescribed antibiotics (22.5%) followed by Azythromycin (11.6%) Cefixime (11.5%) Ciprofloxacin (10.9%) Flucloxacillin (10.9%) and Metronidazole (8.7%). Conclusion: This study revealed that percentage of antibiotic was high and most of the antibiotic was given without culture and sensitivity. Chatt Maa Shi Hosp Med Coll J; Vol.17 (2); Jul 2018; Page 36-39